Model of pre-aeration in pyritic gold concentrate, for optimization of the cyanidation process - Aramburú Rojas, Vidal Sixto (2003)
The sample that is the subject of study is a concentrate mainly of gold pyrite, product of the flotation process, from Empresa Minera Aurífera Calpa S.A. The characterization of the concentrate in the UNMSM polarized light microscope shows the presence of pyrite, sphalerite, chalcopyrite, electrum, marcasite, pyrrhotite, arsenopyrite, rutile and gangue. In the polished briquette corresponding to the +100 mesh, the presence of electrum has been observed. In the scanning electron microscope at the University, the presence of gold particles has been observed, even in pyrite; Said particles have sizes smaller than 200 nanometers, particles of gold and silver telluride intertwined with the electrum are also observed, whose particles have sizes smaller than 2 microns. These characteristics make the concentrate refractory to conventional treatment by the cyanidation process, which constitutes a serious problem due to the high consumption of sodium cyanide and limited recoveries. The present research work is oriented to study new pretreatment schemes such as pre-aeration with lime, which is a process prior to cyanidation. The mathematical model obtained for the pre-aeration process, using the hexagonal design, indicates that the variable that has the greatest influence is pH, followed by time and its corresponding interaction, keeping constant the oxygen concentration, grain size of the concentrate and the dilution of the pulp, as it has little impact on the process. Obtaining a response with an acceptable recovery in the cyanidation process, which is quite significant compared to conventional cyanidation. In summary, the advantages of pre-aeration is that in cyanidation the consumption of sodium cyanide is reduced by 55% and the recovery improves by 10.57%, for this type of concentrate.